Most Significant Change Experienced by Farmers from Adopting Rainforestation Farming - Velarde, Genie Leen M.; Gravoso, Rotacio S.; Cagasan, Editha G.; Gabrillo, Christina A. (Annals of Tropical Research, 2007)
The Visayas State University (VSU) developed the rainforestation farming (RF) system to replace the more destructive forms of kaingin or slash-and-burn practices commonly practiced by farmers and provide them with a stable and higher income. VSU disseminated the technology through training and establishment of demonstration farms coupled with various extension materials. The most important changes experienced by farmers from adopting RF were increase in income, greater social skills, improvement of their water and air conditions, and enhancement of biodiversity in their rainforestation farms.